2021
DOI: 10.7759/cureus.13492
|View full text |Cite
|
Sign up to set email alerts
|

Proxalutamide Significantly Accelerates Viral Clearance and Reduces Time to Clinical Remission in Patients with Mild to Moderate COVID-19: Results from a Randomized, Double-Blinded, Placebo-Controlled Trial

Abstract: Background The entry of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) into type II pneumocytes is dependent on a modification of viral spike proteins by transmembrane protease serine 2 (TMPRSS2) expressed on the surface of human cells. TMPRSS2 is regulated by the androgen receptor, hence, SARS-CoV-2 infectivity is indirectly dependent on androgenic status and phenotype. Previously, we have reported that men affected by androgenetic alopecia (AGA) are overrepresented in severe coronavi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
63
1
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 58 publications
(67 citation statements)
references
References 16 publications
1
63
1
2
Order By: Relevance
“…19 We have previously demonstrating that proxalutamide was effective to prevent hospitalization in COVID-19 male patients and to reduce viral shedding and inflammatory response, in a double-blind, placebo-controlled randomized clinical trial (RCT). 20,21 We have also demonstrated that proxalutamide was able to reduce mortality rate by 77.7% in moderate-to-severe hospitalized COVID-19 patients that were not on mechanical ventilation, and increased recovery speed by 128%, when compared to placebo, also in a double-blind, placebo-controlled RCT.…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…19 We have previously demonstrating that proxalutamide was effective to prevent hospitalization in COVID-19 male patients and to reduce viral shedding and inflammatory response, in a double-blind, placebo-controlled randomized clinical trial (RCT). 20,21 We have also demonstrated that proxalutamide was able to reduce mortality rate by 77.7% in moderate-to-severe hospitalized COVID-19 patients that were not on mechanical ventilation, and increased recovery speed by 128%, when compared to placebo, also in a double-blind, placebo-controlled RCT.…”
Section: Introductionmentioning
confidence: 82%
“…25 Unbalanced actives and placebo distribution across sites and minor protocol modifications were the major weaknesses of the present RCT, while the lack of any modification of the ITT analysis prevented additional biases. 21 Spontaneous erection (males) 4/329 (1.2%) 4/163 (2.5%) 0/166 0.70…”
Section: Discussionmentioning
confidence: 99%
“…15 We have previously reported our preliminary analysis of the effects of proxalutamide 200mg per day in COVID-19 patients, which showed an overall 74% reduction in nasopharyngeal detection of SARS-CoV-2 on the 7 th day of treatment. 16 The objective of this study was to evaluate the e cacy of proxalutamide in preventing hospitalization in males diagnosed with COVID-19 in an outpatient setting.…”
Section: Introductionmentioning
confidence: 99%
“…The COVIDENZA trial led by the University of Gothenburg is an ongoing randomized trial of enzalutamide plus standard of care versus standard of care in hospitalized patients with COVID-19 [ 14 ]. A trial in the outpatient setting recently reported that antiandrogen treatment accelerated viral clearance as compared to placebo [ 15 ]. Whether or not AR antagonism should be considered as a therapeutic strategy for patients hospitalized with COVID-19 will depend on the results of this and related trials.…”
Section: Discussionmentioning
confidence: 99%